Pyrite FeS2 nanobelts as high-performance anode material for aqueous pseudocapacitor. (20th December 2016) - Chen, Jizhang; Zhou, Xiaoyan; Mei, Changtong; Xu, Junling; Zhou, Shuang; Wong, Ching-Ping
Graphical abstract: Highlights: Pyrite FeS2 nanobelts are fabricated by a soft-template-assisted one-pot method. The intrinsic high electrical conductivity of pyrite FeS2 improves performance. The nanostructured morphology facilitates charge transport and lower polarization. The product exhibits considerably improved performance compared to contrast samples. Abstract: To push energy and power limits of aqueous pseudocapacitors, advanced anode materials are highly desirable. In this work, pyrite FeS2 nanobelts are fabricated through a soft-template-assisted one-pot method. The high electrical conductivity and nanostructured morphology of this anode material facilitate charge transports, thus considerably improving pseudocapacitive performance compared to Fe2 O3 and FeS2 contrast samples. This material can deliver a high capacitance of 308.3 F g −1 /317.8 F g −1 at 5 mV s −1 /3 A g −1 . It also exhibits good rate capability that 64.2% and 42.0% of the above capacitance can be retained when the scan rate and current density are increased to 10-fold, respectively, and superior long-term cyclability that 81.1% capacitance retention can be obtained after 1000 cycles. The results demonstrate great potential of pyrite FeS2 anode material for aqueous pseudocapacitors.